Toward combining graphene and QDs: Assembling CdTe QDs to exfoliated graphite and nanographene in water - Katsukis, Georgios; Malig, Jenny; Schulz-Drost, Christian; Leubner, Susanne; Jux, Norbert; Guldi, Dirk Michael (Acs Nano, 2012)
Herein, we report for the first time on a full-fledged investigation of water-soluble CdTe quantum dots (QD) that are immobilized onto exfoliated graphite (EG) and/or nanographene (NG). Particular emphasis was placed on a top-down preparation of stable aqueous dispersions-starting from natural graphite rather than graphene oxide-while preserving the intrinsic properties of graphene. To this end, we circumvented the harsh conditions commonly employed for the pre-exfoliation (i.e., Hummers method). First, a hydrophobic- hydrophobic/π-π stacking motif was tested between EG and pyrene, to which QDs are covalently attached (QD-pyrene). Second, we employed the combination of hydrophobic-hydrophobic/π-π stacking and electrostatic interactions to build up hierarchical structures composed of NG, positively charged pyrene (pyrene ), and negatively charged QDs. The novel nanohybrids-QD- pyrene/EG and QD/pyrene /NG-were characterized with specific emphasis on electron-transfer chemistry. In fact, both assays provide kinetic and spectroscopic evidence that support electron transfer dynamics that vary, however, between EG and NG as a reflection of the different degree of graphite exfoliation. © 2012 American Chemical Society.